Growth of floating hook-moss (Warnstorfia fluitans) differs with nutrient and water flow adjustments in greenhouse and cold room conditions. Issue 1 (January 2023) - Adebayo, Adeyemi; Kiani, Sepideh; Ruotsalainen, Anna Liisa; Pirttilä, Anna Maria; Lehosmaa, Kaisa
Abstract: Floating hook-moss ( Warnstorfia fluitans ) is a bryophyte growing in northern aquatic and peatland ecosystems. W. fluitans uptakes metals and excessive amounts of nitrogen from wastewater, which suggests that it may have commercial potential for use in phytoremediation. Optimization of growth conditions would allow artificial cultivation of floating hook moss in large quantities for phytoremediation applications. We tested how application of combined nutrient (NPK 7-2-2 ranging from 0.1 to 1 ml per liter of water) and water flow (ranging from 0.15 to 1.9 ml/min) treatments affect growth of W. fluitans in greenhouse conditions. At the end of the experiment, all treatment combinations were subjected to an additional cold room condition at low temperature (0–2 °C) without constant water flow. The moss generally produced biomass in the various treatment combinations. However, contrary to our expectations, we found that increase of nutrients and water flow had a negative effect on the growth of W. fluitans . The highest growth rates in the experiment were detected in the control unit that had no nutrient addition or applied water flow. Our results suggest that cold temperatures are beneficial for W. fluitans growth. Our results show that the commercial production of W. fluitans may not require nutrient or water flow manipulation, at least in the tested scale. Instead, the growth conditions should mimic the natural cold climate conditions of W. fluitans habitats in northern peatlands and/or spring ecosystems.